2013
DOI: 10.1089/end.2013.0345
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Hyaluronic Acid-Carboxymethylcellulose Adhesion Barrier on the Neurovascular Bundle and Prostatic Bed to Facilitate Earlier Recovery of Erectile Function After Robot-Assisted Prostatectomy: An Initial Experience

Abstract: Purpose: To investigate the efficacy of hyaluronic acid-carboxymethylcellulose (HACM) in facilitating early recovery of erectile function (EF) after radical prostatectomy, we report our initial experience of HACM use on the neurovascular bundle (NVB) after robot-assisted radical prostatectomy (RARP). Patients and Methods: Between 2008 and 2010, 459 consecutive patients who underwent RARP with bilateral nerve-sparing technique were included in this study. Patients were classified into two groups: HACM (group 1;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…However, covering the prostate bed with HA/CMC did not increase including postoperative urine leakage or other complications in the present study, even though RP involves vesicourethral anastomosis. Joung et al reported earlier recovery of erectile function when the neurovascular bundle was coated with HA/CMC gel during RARP than in the control group [26]. They also reported that complication rates did not differ between the two groups, a similar finding to the results of the present study.…”
Section: Discussionsupporting
confidence: 89%
“…However, covering the prostate bed with HA/CMC did not increase including postoperative urine leakage or other complications in the present study, even though RP involves vesicourethral anastomosis. Joung et al reported earlier recovery of erectile function when the neurovascular bundle was coated with HA/CMC gel during RARP than in the control group [26]. They also reported that complication rates did not differ between the two groups, a similar finding to the results of the present study.…”
Section: Discussionsupporting
confidence: 89%
“…In the majority of cases these agents function as a physical barrier to separate wound areas at risk of developing adhesions. These devices include adhesion barriers made from oxidized regenerative cellulose 6, polytetrafluoroethylene 7, icodextrin 8, hyaluronic acid/carboxymethyl cellulose 9 and starch 10. Typically, starch-based products are used solely as hemostats, such as Arista™ AH (Arista; Davol Inc., USA) 11.…”
Section: Introductionmentioning
confidence: 99%
“…From anatomic studies, we know that it is important to spare the nerve plexus, which is located individually, with numerous fibers, and is challenging to visualize. Studies have explored neuropraxia during radical prostatectomy, but few use tissue engineering to protect the pelvic nerve plexus [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%